The epidemiology of bacterial zoonoses in pastoral and dairy cattle in Cameroon, Central Africa. (15th June 2021) - Kelly, Robert F.; Jennings, Amy; Hunt, Jennifer; Hamman, Saidou M.; Mazeri, Stella; Nkongho, Egbe F.; Ngwa, Victor N.; Tanya, Vincent; Sander, Melissa; Ndip, Lucy; Bessell, Paul R.; Morgan, Kenton L.; et al.
Abstract: Previous work identified that bacterial zoonoses ( Brucella species, Coxiella burnetii and Leptospira hardjo) were present in Cameroonian pastoral cattle. To assess the characteristics of this zoonotic risk, we analyse seroprevalence of each pathogen and the associated management, herd and environmental factors in Cameroonian pastoral and dairy cattle. Cross‐sectional samples included pastoralist herds in the Northwest Region (NWR n = 750) and Vina Division (VD n = 748) and small holder dairy herds in the NWR ( n = 60). Exposure to Brucella spp., C. burnetii and L. hardjo were screened for using commercial ELISAs and population adjusted estimates made. In addition, individual, herd and ecological metadata were collected and used to identify risk factors associated with animal‐level seropositivity. In the pastoral cattle, seroprevalence to Brucella spp . was relatively low but was higher in the NWR (4.2%, CI: 2.5%–7.0%) than the VD (1.1%: CI 0.5%–2.4%), while L. hardjo seroprevalence was much higher though similar in the NWR (30.7%, CI 26.3%–35.5%) and VD (35.9%, CI 31.3%–40.7%). No differences were noted in C. burnetii seroprevalence between the two study sites (NWR: 14.6%, CI 11.8%–18.0%. VD: 12.4%, 9.6%–15.9%). Compared to pastoral, dairy cattle had lower seroprevalences for L. hardjo (1.7%, CI: 0.0%–4.9%), C. burnetii (0.0%, CI 0.0%–6.0%) but similar for Brucella spp. (5.0%, CI 0.0%–10.6%). Increased odds of Brucella spp . seropositivity were associated with owning sheep or rearing sheep and fencing cattle in at night. Adult cattle had increased odds of being seropositive for both C. burnetii and L. hardjo . Additionally, exposure to C. burnetii was associated with local ecological conditions and L. hardjo was negatively associated with cattle undertaking transhumance. This work highlights that exposure to these 3 important production diseases and occupational zoonoses are widespread in Cameroonian cattle. Further work is required to understand transmission dynamics between humans and livestock to inform implementation of effective control measures.